Monetary policy and wealth inequality over the great recession in the UK: An empirical analysis - Haroon Mumtaz; Angeliki Theophilopoulou (Queen Mary University of London, School of Economics and Finance, 2019)
We use detailed micro information at household level from the Wealth and Assets Survey to construct measures of wealth inequality from 2005 to 2016 at the monthly frequency. We investigate the dynamic relationship between monetary policy and the evolution of wealth inequality measures. Our findings suggest that expansionary monetary policy shocks lead to an increase in wealth inequality and contributed significantly to its fluctuations. This effect is heterogenous across the wealth distribution with the monetary shock affecting the median household relative to the 20th percentile by a larger amount than the right tail. Our results suggest that the shock is transmitted through changes in net property and financial wealth that constitute the bulk of total wealth of households near the median of the wealth distribution.
Keywords: D31; E21; E44; E52; 330; Inequality; Wealth; FAVAR; Monetary Policy Shocks